Assessment of process management maturity in developing countries based on SAW method - Radosavljevic, Marija (Journal of Business Economics and Management, 2014)
Business process management is a comprehensive, holistic management approach, aligned with the context that proceeds from globalized economy. The extent to which this approach is present in an organization represents its process management maturity. Process management maturity has drawn attention of authors and, consequently, a lot of maturity models have appeared. These models incorporate elements, which determine the level of organizations’ maturity. Earlier research results indicate that those elements are mutually related and responsible for organizations’ performances. Since those results mostly refer to developed countries, the question is whether conclusions that proceed from them are valid for developing countries too. In order to answer this question, research has been conducted in Serbia. The aim of the research is to discover which maturity model elements represent the weak points of business process management in Serbian organizations, but also to evaluate the dependence of organizations’ performances on process management maturity level. The analysis is based on statistics tools and Simple Additive Weight (SAW) method. Research results indicate that the maturity level of the Serbian economy is not enviable. In addition, results suggest that business performances might be connected to process management maturity, in the sense that higher maturity level means higher performances.